INFLUENCE OF MASS INFORMATION ON GENDER ROLE IN JAPAN’S SOCIETY - Л.Д. Нурсеитовa; Т., Ниномия (Journal of Oriental Studies, 2019)
This article is devoted to the phenomenon of recent decades as the influence of the media on gender roles in Japanese society. The media is an integral part of society, and a platform for discussion and the definition of new «norms» in the 21st century the century of the information age. And often in the mass media, in connection with the changes taking place in the world, issues related to gender are raised, which, as a rule, determine stereotypes, forming general ideas about the representation of women, men and gender relations in society. Japanese media are no exception. They also represent a prism through which we see gender roles and the position of women in politics, economics and other areas of activity in society. Key words: japanese women, World War II, modern period, society, equality, independence, man, discrimination, democracy.